(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
This study aimed to investigate the role of physical manipulatives in building pre-service teachers’ conceptual understanding of fractions. Using a quasi-experimental design, one hundred fifty (150) pre-service teachers were chosen based on purposive sampling. Before implementing the five-week intervention design, which was based on manipulatives, an initial test was conducted. To collect additional data for the study, a second test was administered immediately after the intervention to supplement the pre-intervention test. The statistical analysis revealed a Pretest (mean = 9.11, standard deviation = 4.863), and a Post-test (mean = 21.60, standard deviation = 6.021). The null hypothesis was rejected using the t-test, which revealed (P = 0.00 < 0.05) at a confidence level of 95%, as there was a statistically significant difference in the performance of Pre-service teachers between the two tests. Therefore, the researchers recommend that fractions be taught using manipulatives in colleges of education.